(untitled) (diségno, 2020)
In the third century BC, it happened that Eratosthenes of Cyrene (a city located in today’s Libya) wanted to measure the radius of the earth, and he tried to do so using the instruments that were available to him at the time. The experiment gave an incredible result, obtaining a measurement that differs only 5% from the value currently known. The merit of Eratosthenes was to make a measurement with a good degree of accuracy using only one instrument: the gnomon, which is a stick planted vertically in perfectly flat, level ground [1]. (read more)